Group Work, Students' Reading Ability, and Motivation - Wahidah, Farah Sukmawati (Universitas Swadaya Gunung Jati, 2014)
Teachers must be able to cooperate with their students in the class to make the teaching and learning activities enjoyable. A good teacher has to use appropriate strategies to make his or her students fluent readers. Teachers also have to make students feel comfortable so that they can achieve the objective of the teaching and learning activities. Responding to the problems and considering the factors causing them, the researcher taught that the best way to improve the students' reading ability is through group work. Group work is a group of students who work together. Students in group can share, compare, and contrast ideas and thoughts. Group work enables students to study more because they learn together in an enjoyable way. Students will be motivated to study because working in group makes them help each other, especially when facing difficulties in reading. Students can get the meaning of some vocabularies and the content of the text easily. This research showed that group work can improve students' reading ability and motivation.